Accountability and effectiveness evaluation in non-profit organizations - Cutt, James, 1937- (Routledge studies in the management of voluntary and non-profit organizations, 2000)
This unique volume provides new perspectives on assessing the performance of nonprofit organizations whilst meeting the information needs of decision-makers, both internal (such as resource-providers, regulators and clients), and external (including boards, managers, staff and volunteers). Whilst most discussions of accountability focus exclusively on financial accountability, this title offers a significant contribution to a relatively untouched area by combining the treatment of both evaluation and accountability from a managerial perspective. With increased interest in the co.